A audiência telepresencial e a segurança jurídica no processo do trabalho - Silva, Michel Borges da (2022)
The dissertation proposes an in-depth research on the procedural law of labor and the new technological dictates that involve the procedural acts of conflict resolution. Uncontroversial is that one day we would all be facing screens, devices, state-of-the-art cell devices and even technologies with artificial intelligencecapable of reading, interpreting and conducting human thought in an automated way. Without prejudice to the technological procedural evolution faced, it is necessary to highlight a certain acceleration with regard to the forced improvement of the electronic judicial system, because with the arrival of a highly contagious disease, such technological developments had to be shaped to the social moment experienced, even requiring an improvement in access to justice, with the effort to make it more safe, fast and effective, by handing over the desired judicial protection. The forced implementation of technology in favor of article 5, item XXXV of the Magna Carta, should be observed with some caution, because the evolution of labor law with regard to the virtual environment was somewhat accelerated due to the disease that plagued the world (COVID-19), bringing disorganized growth and development, but inevitable. The world accustomed to human warmth, various greetings, reserved conversations, hearings, trial sessions, memorial deliveries in offices, procedural orders, various meetings, among other face-to-face forms of problem solving, had to simply follow health protocols overnight as a way to combat the highly infectious deadly virus. We could see, from the outbreak of COVID-19, how fragile and dependent we are of the human relationship, and how well-used technology serves to improve social and legal aspects, because the accelerated implementation of tele-face-to-face means served to teach us that it is possible to establish new safe and efficient procedural rites for both legal professionals, and for those who seek justice as a means of resolving conflicts related to legal assets of life. The proposal is to demonstrate concrete studies by limiting the main impacts on time and space, with the repercussion of the main changes proposed by anticipating the technological future, and how this can be used for the benefit of society and all who toil in the dealings before the poder judiciário, while fulfilling the fundamental role of the state called access to justice with due effective legal certainty and guarantor of fundamental rights